Electrical and Thermoelecrtical Behavior of Binary Composites of Phosphate Glass Loaded with Zinc Fillers: Promising Materials for Photovoltaic's. Issue 11 (6th November 2015) - Hammi, M.; Aziate, G.; Pinto, G.; Maaroufi, A.
Abstract: Homogeneous xPbO−(1−x) P2 O5 glasses where 0 % :σ x<100 % have been successfully synthesized using a melt‐quenching method. The short range structures of the prepared samples were examined by Fourier transform infrared spectroscopy, x‐powder diffraction and scanning electron microscopy. The most stable vitreous phase is of composition 45 mol%PbO‐55 mol%P2 O5 ; it was loaded with zinc volume fraction. We carried out experimental and simulative investigations of the electrical characteristics of pn junction; the obtained results indicated that conductivity of the composites increases by increasing dopent concentration. It was also observed that the current voltage characteristics of the composite were found to be ohmic in nature, wherein drastic drop of the electrical conduction was observed at an accurate temperature of 405 K. Electrical behavior of the composites as function of filler concentration and versus temperature were explained respectively by percolation theory and positive temperature coefficient effect. Abstract : In this paper, we focus on studying the essential physical properties of Zn/PbOP2 O5 bulk composites. As depicted in the figure against, the thermoelectrical behaviour is substantially evaluated; the doping element could be considered as the primary origin of the electrical conductivity in the doped glass system. The Zn‐doped glass samples demonstrate high electrical conductivity then it is slightly decreasing until critical temperature point in which occurs a drastic drop of conduction, this is due to the thermal expansion of the host material, this phenomenon is pretty interpreted by the so called PTC effect.